Supply and demand: Recentring the multilateral debate on the Atlantic - Seabra, Pedro (United Nations University-Comparative Regional Integration Studies (UNU-CRIS) Research Seminar, 2024)
Amid the growing narrative of a crisis of international multilateralism, collective frameworks are increasingly questioned across the board. In parallel, the Global South has sought to stake new claims over existing institutional options with the aim of reframing the debate. How have such developments found correspondence in terms of the Atlantic and how to understand this space from a multilateral point of view? This communication argues that the specificities found in this regional space help to better understand the evolution of institutional provision in recent years. With a focus on the challenges and opportunities associated with informal cooperation dynamics, the scope and results of existing governance mechanisms for the Atlantic are analysed. Dynamics of overlapping multilateral supply and demand, coupled with recurrent operational irregularity are identified as the key elements that allow to properly characterize this regional space.